GAMBARAN KEJADIAN PENYAKIT MALARIA DIWILAYAHKERJA PUSKESMAS RAWAT INAP KATIBUNG KECAMATAN KATIBUNG KABUPATEN LAMPUNGSELATANTAHUN 2020 - Antini, Novita Putri (Health Publica, 2020)
AbstractMalaria is a disease caused by the intracellular oblivious protozoa of the Plasmodium genus of the disease is naturally transmitted by a mosquito bite Anopheles females. Hospitalisation of Katidude is the largest area of malaria disease in South Lampung regency. To know the incidence of malaria disease in the implementation of malaria eradication through the main vector control efforts, namely Anopheles in the work area of hospitalization of Katidude in the district Katidude district of South Lampung in 2019. This research is descriptive, to know the incidence of malaria disease in the implementation of malaria eradication through the main vector control efforts of Anopheles in the work area of hospitalisation of Katidude District Katidude Regency of South Lampung in 2020. Conducted from June to April 2020. Malaria Vector control efforts are physically used with insecticide (28.9%), gauze wire installation (18.1%) And the use of electric rackets (8.4%). Biobiology (6%) Use tilapia type (6%). Chemically use mosquito repellent (73.5), Larvaciding (56.6%), and malaria spraying (0%) Through environmental management, water drying (68.7%), removal of moss (84.3%) and crop cleansing (77.1%). It is hoped that people who already have mosquito nets to use when sleeping at night and for those who do not have mosquito nets should do the distribution of ordinary mosquito nets. It is expected that people who already have fish ponds added a pet to the fish-eating flick in order to reduce the mosquito population of mosquitoes Anopheles. It is hoped that people better prioritize other types of vector control. Hopefully people better pay attention to hygiene in environmental management.Keywords: Anopheles mosquito, vector control, malaria disease, plasmodium, vectorAbstrakMalaria adalah suatu penyakit yang disebabkan oleh protozoa obligat intraseluler dari genus plasmodium penyakit ini secara alami ditularkan oleh gigitan nyamuk Anopheles betina. Puskesmas Rawat Inap Katibung merupakan daerah terbesar penyakit malaria yang ada di kabupaten lampung selatan. Untuk mengetahui kejadian penyakit malaria dalam pelaksanaan pemberantasan malaria melalui upaya pengendalian vektor utama yaitu Anopheles di wilayah kerja Puskesmas Rawat Inap Katibung Kecamatan Katibung Kabupaten Lampung Selatan Tahun 2019. Penelitian ini bersifat deskriptif, untuk mengetahui kejadian penyakit malaria dalam pelaksanaan pemberantasan malaria melalui upaya pengendalian vektor utama yaitu Anopheles di wilayah kerja Puskesmas Rawat Inap Katibung Kecamatan Katibung Kabupaten Lampung Selatan Tahun 2020. yang dilaksanakan pada bulan Juni sampai April 2020.Upaya pengendalian vektor malaria secara fisik menggunakan kelambu berinsektisida (28,9%), pemasangan kawat kasa (18,1%) dan penggunaan raket elektrik (8,4%). Secara biologi (6%) menggunakan jenis ikan nila (6%). secara kimia menggunakan obat anti nyamuk (73,5), Larvaciding (56,6%), dan penyemprotan malaria (0%) Melalui pengelolaan lingkungan, pengeringan genangan air (68,7 %), pengangkatan lumut (84,3%) dan pembersihan tanaman (77,1 %). Diharapkan masyarakat yang sudah mempunyai kelambu agar digunakan saat tidur di malam hari dan untuk yang belum mempunyai kelambu berinsektisida sebaiknya dilakukannya pendistribusian kelambu biasa. Diharapkan masyarakat yang sudah mempunyai kolam ikan ditambahkan peliharaan ikan pemakan jentik supaya dapat menurunkan populasi jentik nyamuk Anopheles. Diharapkan masyarakat lebih baik mengutamakan pengendalian vektor jenis lainnya. Diharapkan masyarakat lebih baik memperhatikan kebersihan dalam pengelolaan lingkungan. Kata kunci: Nyamuk anopheles, pengendalian vektor, penyakit malaria, plasmodium, vektorÂ